Case Report: Food-based enteral formula in the nutritional management of children with hyperinsulinism: single center retrospective case series - O’Connor, Graeme; Cheng, Lauren; Cunjamalay, Annaruby (Frontiers in Endocrinology, 2025)
ContextHyperinsulinism is characterized by dysregulated insulin secretion and is typically associated with reduced fasting tolerance. Long-term hyperinsulinism management includes nutrition and medication to normalize plasma glucose levels. Management of enteral feeds and oral intake is integral to the clinical management strategy in children with hyperinsulinism. A new generation of commercial Food Based Enteral Formulas (FBF) consists of rehydrated food, whole‐food protein sources and a mixture of soluble and insoluble fiber.ObjectiveReview the tolerance of a food-based enteral formula for the nutritional management of children with hyperinsulinism.MethodsA single-center retrospective case series to explore the dietetic practice of prescribing a commercially available FBF (Compleat® pediatric, Nestlé Health Science) in children with congenital hyperinsulinism (CHI) or postprandial hypoglycemia (PPH). Data were collected on demographics, gastrointestinal symptoms, anthropometrics, percentage glucose management indicators (GMI%) and hypo/hyperglycemic episodes.ResultsData were collected on eight children; six were diagnosed with CHI and two children had PPH. The mean age was 1.4 years (0.4SD). All children had a gastrostomy for enteral nutrition. Six of the eight children were prescribed proton pump inhibitors or stool softeners to manage gastroesophageal reflux and/or constipation symptoms. Within one month of children being prescribed FBF dietitians documented an 80% improvement in gastrointestinal symptoms. Dexcom glucose data was available for six children. Six months after FBF was prescribed, Dexcon Inc. data reported that five children had an improvement or stable GMI% and all six children had a reduction in hyperglycemic episodes (chi-square =5.8, p-value 0.02). Children prescribed FBF were less likely to require a glucose polymer (Chi-square = 4.9, p-value = 0.02).ConclusionOur retrospective case series suggests that FBF is well tolerated in children with hyperinsulinism and may mitigate gut motility issues associated with hyperinsulinism, especially in relation to gastro-esophageal reflux and constipation symptoms. Furthermore, FBF may help reduce the dependency on glucose polymers and reduce the likelihood of a hyperglycemic episode. A larger sample size and longer follow-up study are necessary to substantiate the potential beneficial impact of FBF’s on glucose control in children with hyperinsulinism.